Obstacles and challenges in implementing and applying shared parenting principle in Malaysia - Ali, Suzana; Che Soh @ Yusoff, Roslina; Mohd Zin, Najibah (Lexis Nexis, 2017)
Malaysian legislations on child custody emphasise that welfare of the child shall be the paramount consideration. However, the legislations do not have any provisions on shared parenting principle and specific guidelines on its implementation and application. Amendments were made to laws to include a provision of equal parental rights but it does not directly relate to the principle of shared parenting which emphasises on the parental responsibilities. The vagueness of the laws and the absence of the proper guidelines in relation to shared parenting opens the doors for the courts to have inconsistent decisions in determining custodial rights and often decide in favour of sole custody. The absence of specific laws on shared parenting has also caused difficulties for the parents to cooperate for the sake of the children. They have a tendency to focus on their conflicts and fighting for their own rights rather than to focus on the welfare of the children as they do not know or have limited knowledge on the significance of practicing shared parenting. This article seeks to discuss the obstacles and challenges in implementing and applying shared parenting after marital separation in Malaysia. A very brief comparative overview on the application of shared parenting in Australia is explained to see how they go about with this concept. As Malaysia practises a dual legal system, this article will examine the suitability of the shared parenting principle to be applied in both systems. Analysis of cases from the Civil and Shariah Courts will be made to identify the extent of the courts' effort in applying the principle. Finally, this article will provide comments and suggestions to improve the current law in Malaysia.